MODERN HIGH-SENSITIVE TROPONIN DIAGNOSTIC METHODS IN ASSESSMENT OF MYOCARDIAL ISCHEMIA AND PROGNOSTICAL VALUE FOR CHRONIC CORONARY HEART DISEASE - L. V. Kremneva; S. N. Suplotov; S. V. Shalaev (Российский кардиологический журнал)
While using the highly sensitive tests  of troponins (hs-CTn), increased levels above the  lower limit can  be  found  in most  of patients,   and  levels  more  than  99th percentile  — in about  10-15%  patients  with stable  angina.  The grade  of hs-cTn increase correlates with severity of coronary lesion and level of myocardial ischemia. Elevated  levels  of  hs-cTn  are  associated  with increased  risk  of  general   and cardiovascular mortality, as hospitalizations due to chronic heart failure.